2023
DOI: 10.1038/s41598-023-35879-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole strains vs MGEs in short and longterm transmission of ESBL genes between healthcare and community settings in Uganda

Abstract: Multidrug-resistant ESBL-producing Escherichia coli are a leading cause of infections in hospital and community settings. Based on samples from two hospitals in Uganda and households of inpatients we tested the hypothesis that ESBL E. coli and/or their resistance determinants could spread within the healthcare and community settings through discharged patients that were still colonized. We used bacterial culture, susceptibility testing whole genome sequencing and detailed bioinformatics analysis to test the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The fact that all our isolates, except three, carried plasmids signifies a serious problem, especially within healthcare settings, and calls for more dedicated infection control measures to eliminate them from such facilities. Our previous studies have indeed demonstrated a higher prevalence of resistance in E. coli from healthcare environments but also from healthcare workers who may be serving as sources of infection with resistant bacteria to hospitalized patients [16].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The fact that all our isolates, except three, carried plasmids signifies a serious problem, especially within healthcare settings, and calls for more dedicated infection control measures to eliminate them from such facilities. Our previous studies have indeed demonstrated a higher prevalence of resistance in E. coli from healthcare environments but also from healthcare workers who may be serving as sources of infection with resistant bacteria to hospitalized patients [16].…”
Section: Discussionmentioning
confidence: 83%
“…The isolates were subjected to antimicrobial susceptibility testing against 17 antibiotics by disc diffusion assay as previously described [16] on Mueller-Hinton agar (MHA) (Oxoid, Manchester, UK). A suspension of 0.5 McFarland standard turbidity was spread on the surface of MHA plates using a sterile cotton swab.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%
“…A CTX-M-15 encoding 180-kb IncFIIK plasmid in K. pneumoniae ST17 has been stably maintained for up to 2 years in colonised patients [38]. Furthermore, a recent study has demonstrated the long-term transmission of AMR, including ESBL genes, between healthcare and community networks can be facilitated by the transmission of plasmids circulating across niches [39]. High colonisation rates, combined with long-term persistence and plasmid transfer, may engender a scenario for future dissemination of ST628 and its CTX-M-15 encoding plasmid.…”
Section: Discussionmentioning
confidence: 99%